Caracterização de painéis aglomerados com madeira de eucalipto e sólidos granulares de poliuretano - Rauber, Renata (2011)
The objective of the present study was to evaluate the performance of particleboards fabricated with different proportions of Eucalyptus grandis Hill ex Maiden wood and polyurethane granular solids from the footwear sector of Três Coroas/RS city, using as a binding agent Elastan 8004/BR®, a pre-polymer modified polyisocyanate MDI based. The proportions of polyurethane granular solids and wood particles used were 0/100, 15/85, 30/70, 45/55 e 60/40% (m/m). The performance of the panels was evaluated by density, moisture content, water absorption and thickness swelling at 2 and 24 hours, tensile strength perpendicular to surface, hardness testing, screw withdrawal, IZOD impact strength, thermal conductivity and acoustic performance in relation to airborne noise. Polyurethane addition caused an increase in dimensional stability of the panels, reducing the values of water absorption and thickness swelling. Tensile strength perpendicular to surface of the panels increased significantly with the increase of polyurethane amount in the composition, indicating adhesion quality between particles of panel and adhesive used. Hardness testing was negatively influenced, indicating that the values decreased with the increasing of polyurethane amount. The highest values of screw withdrawal were found using 30 and 45% (m/m) of polyurethane. The IZOD impact strength of the panels increased with the polyurethane granular solids incorporation in its composition, requiring more energy to break them. The addition of t polyurethane provided a decrease in the values of thermal conductivity of the panels and affected the acoustic performance of the panels in a positive way.